(untitled) (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Ismail A, Hakim NSA, Radzun KA, Pardi F, Latif MT, Ikhsan NAK, Hidayati D, Buyong F. 2024. Abiotic factors and distribution patterns of epiphytic lichens inhabiting different altitudes. Biodiversitas 25: 3084-3094. Lichens are a symbiotic partnership of two separate organisms, a fungus, and an alga. Although many species of lichens exist in Malaysia, comprehensive data on lichens are still being determined. Thus, this study provides significant knowledge for the researcher to gain more understanding and information on the lichen species in Malaysia and how the abiotic factors affect the community. This study aimed to identify lichen species taxonomically, assess species composition, and compare the lichen species coverage in two sampling stations with contrasting altitudes: Brinchang in Cameron Highland (high altitude, 1,428 masl) and Templer Park in Rawang (low altitude, 131 masl). This study presented sound evidence on the relationship between lichen species coverage and abiotic factors such as bark pH, relative humidity, temperature, and atmospheric gas (ammonia), which provide knowledge on lichen diversity. Lichen sampling used a 30×50 cm quadrat on the tree trunk, 1 m above the ground. As a result, a species description table was constructed for 18 lichen species from 9 families and 15 genera. Out of these genera, the crustose group dominates at 72%, the foliose group at 22%, and the fruticose group at 6%. The low altitude recorded significantly higher species coverage, 63.47±5.59%, while the high altitude showed lower species coverage, 46.56±3.08%. The mean temperature of low altitudes is significantly higher at 32.01°C compared to the high altitudes (23.87°C). However, the relative humidity and bark pH within these altitudes were not significantly different. The mean concentration of NH3 at low altitudes was considerably higher at 0.40±0.07 ppm than at high altitudes (0.11±0.04 ppm). It was shown that the fruticose group increased as the altitudes increased. In contrast, crustose lichen is reduced in coverage and number of species compared to high altitudes. This study concluded that inter-related abiotic factors related to the altitudes facilitated the survival of the lichen community in the sampling areas.